The effect of temperature regimes on laboratory germination rates and germination energy of Astragalus L. - T. V. Kornievskaya (Труды по прикладной ботанике, генетике и селекции)
Background. The temperature regime has a significant effect on the enzymatic activity of seeds. Optimum temperatures trigger physical and chemical reactions in the seed and initiate its germination. The optimum temperature depends on the environmental and geographical conditions in the area of a taxon’s origin and is determined experimentally.Materials and methods. The target material of the study were seeds of three Astragalus L. species (A. cicer L., A. onobrychis L., and A. sulcatus L.) collected from young generative plants introduced in the dry-steppe zone of Kulunda. The effect of temperature conditions (+4…+8°C, +10…+20°C, +20…+32°C) and species-specific attribution of Astragalus plants on laboratory seed germination percentage and energy was studied using the two-factor analysis of variance. The assessment of laboratory seed germination was carried out according to the guidelines by M. M. Ishmuratova and K. G. Tkachenko.Results. The analysis of variance showed a significant effect of the temperature regime (51–54%) and species specificity (23–24%) on the germination percentage rate and germination energy of Astragalus seeds. The seeds of A. onobrychis germinated under a wide range of positive temperatures (from +4…+8°C to +20…+32°C). The temperature range of +10…+20°C was optimal for A. onobrychis and A. sulcatus, with 100% germination. The optimum temperature that determined the maximum laboratory germination of A. cicer seeds was in the range of +20…+32°C. Low positive temperatures (+4…+8°C) were not effective for germination of A. cicer seeds.Conclusion. The optimum temperature conditions for germination of Astragalus seeds were identified: +10…+20°C for A. onobrychis and A. sulcatus, and +20…+32°C for A. cicer.